2012
DOI: 10.1111/j.1834-7819.2012.01702.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of halogen light irradiation on hydrogen peroxide bleaching: an in vitro study

Abstract: Background: The aim of this study was to evaluate the effect of halogen light irradiation on hydrogen peroxide (HP) bleaching by assessing HP concentrations, tooth whitening efficacy, and temperature variations in bleaching agents and pulp chambers. Methods: Sixteen premolars were randomly divided into two groups: Group BL (bleaching agent with halogen light irradiation for 3 · 10 minutes) and Group B (bleaching agent alone). HP concentrations were tested before and after treatment. CIE L*a*b* values of specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
1
12
0
3
Order By: Relevance
“…So in both of these study groups, teeth were exposed longer to QTH light. Relapse in treatmentin the Polydorous study only occurred in a month after treatment QTH group (Polydorou et al, 2013), which is similar to the results of our study, while both groups in the Liangs study showed relapse after a week with or without light cure system (Liang et al, 2012).…”
Section: Groups Bioscience Biotechnology Research Communicationssupporting
confidence: 89%
See 4 more Smart Citations
“…So in both of these study groups, teeth were exposed longer to QTH light. Relapse in treatmentin the Polydorous study only occurred in a month after treatment QTH group (Polydorou et al, 2013), which is similar to the results of our study, while both groups in the Liangs study showed relapse after a week with or without light cure system (Liang et al, 2012).…”
Section: Groups Bioscience Biotechnology Research Communicationssupporting
confidence: 89%
“…For other groupsin the Polydorous study, relapse occurred after 3 months (Polydorou et al, 2013), while in Liangs it happened sooner (Liang et al, 2012). These results can be explained by a lower concentration of bleaching agent used in study (32% Beyond II Advanced Formula Whitening Gel) compared with current study (37.5% Polaoffi ce and 40% Opalescence Boost) and Polydorou study (38% Opalescence Boost), although this difference is negligible.…”
Section: Groups Bioscience Biotechnology Research Communicationsmentioning
confidence: 53%
See 3 more Smart Citations